3D CRISPR screen in prostate cancer cells reveals PARP inhibitor sensitization through TBL1XR1-SMC3 interaction - Zhang, Huan; Gao, Huanyao; Gu, Yayun; John, August; Wei, Lixuan; Huang, Minhong; Yu, Jia; Adeosun, Adeyemi A.; Weinshilboum, Richard M.; Wang, Liewei (Frontiers in Oncology, 2022)
Poly(ADP-ribose) (PAR) polymerase inhibitors (PARPi) either have been approved or being tested in the clinic for the treatment of a variety of cancers with homologous recombination deficiency (HRD). However, cancer cells can develop resistance to PARPi drugs through various mechanisms, and new biomarkers and combination therapeutic strategies need to be developed to support personalized treatment. In this study, a genome-wide CRISPR screen was performed in a prostate cancer cell line with 3D culture condition which identified novel signals involved in DNA repair pathways. One of these genes, TBL1XR1, regulates sensitivity to PARPi in prostate cancer cells. Mechanistically, we show that TBL1XR1 interacts with and stabilizes SMC3 on chromatin and promotes γH2AX spreading along the chromatin of the cells under DNA replication stress. TBL1XR1-SMC3 double knockdown (knockout) cells have comparable sensitivity to PARPi compared to SMC3 knockdown or TBL1XR1 knockout cells, and more sensitivity than WT cells. Our findings provide new insights into mechanisms underlying response to PARPi or platin compounds in the treatment of malignancies.